Using different statistical models to estimate the optimal methionine+cysteine to lysine ratio for male Cobb500 broilers: Growth performance, body composition, and meat yields - de Aguiar, Gustavo A.C.C.; do Nascimento, Mariana A.; Furlani, Nathana R.; Alves, Warley J.; Da Silva Viana, Gabriel; Naranjo, Victor D.; Hannas, Melissa I. (Elsevier, 2025)
Methionine (Met) is a vital sulfur amino acid essential for the survival, growth, and reproduction of poultry, - one which participates on multiple metabolic processes than exclusively protein synthesis. As feed ingredients naturally contains insufficient amounts of Met and cysteine (Cys), synthetic Met sources are commonly supplemented in feeds. The proper balance of Met and Cys is important not only for protein synthesis but also for improving feed efficiency and reducing environmental impacts, such as nitrogen emissions and water consumption. This study explored the effects of different digestible methionine + cysteine to lysine (Met+Cys:Lys) ratios on male Cobb500 broiler chicken performance across three growth phases: starter, grower, and finisher. The findings revealed that as birds matured, their Met+Cys:Lys ratios initially increased and then slightly decreased. Optimizing this ratio not only enhances growth and feed efficiency but also results in leaner carcasses with higher protein and mineral content. Additionally, these adjustments provide economic benefits by lowering feed costs and producing meat with less fat, resulting in a higher-quality product. This research emphasizes the importance of adjusting amino acid ratios based on growth phase to improve both broiler performance and meat yield.
Keywords: ideal protein; sulfur amino acids; productive performance; poultry